EXPLORING THE COGNITIV IMPACT OF THE –INGON LNGUAGE COMPREHENSIONE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The English suffix -ing, encoding both the gerund and present participle forms, constitutes a morphosyntactic marker with multifaceted roles in language structure and use. This paper offers a comprehensive exploration of the cognitive impact of the -ing form on language comprehension, focusing on its morphosyntactic functions, effects on sentence parsing, semantic interpretation of temporal and aspectual distinctions, and implications for working memory load during real-time processing. Synthesizing findings from psycholinguistics, neurolinguistics, and corpus linguistics, the article demonstrates that the -ing form is a vital cue informing event structure and facilitating predictive parsing mechanisms. Moreover, this form interacts dynamically with cognitive control processes during ambiguity resolution and elicits distinct neurophysiological responses reflecting its grammatical complexity. Cross-linguistic evidence from second language acquisition studies and clinical data from aphasia patients further underscore how critical the appropriate processing of the -ing form is for fluent comprehension and production. Future interdisciplinary research integrating neurocognitive methods with naturalistic language data is recommended to broaden understanding of how aspectual markers modulate language comprehension and cognition.